Analysis of Factors Related to Employee Career Development - Ari Kuntardina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
In an effort to face global competition and improve performance, a telecommunications company is trying to streamline itself by implementing an early retirement policy. The policy is primarily intended for senior employees who are less able to keep up with technological developments. However, early retirement policies are more attractive to employees who are younger and have high abilities and potential. They feel that with their abilities and potential they can get new jobs and career development in other companies. This study aims to explain and examine the relationship model of work motivation, individual environment, work ability, employee performance with their career development. The research design is in the form of causal explanation from a survey of three branch offices of telecommunication companies located in Blitar, Malang, and Pasuruan. The research sample was 255 people, the respondents were taken by proportional systematic random sampling. data collection through questionnaires. Data analysis used multiple regression analysis and path analysis. The results of the study indicate that the individual environment is the initial state that stimulates the emergence of work motivation which is a driving force for work ability so as to spur employee performance which in turn can develop their careers.